Cardiotropic medicinal products of plant origin. Prospects for use in modern clinical practice - Nadezhda V. Nesterova; Natalia D. Bunyatyan; Irina A. Samylina; Vladimir A. Evteev (Research Results in Pharmacology)
Introduction: The aim of the research was to study the current state of use and improvement of the prospects for the using cardiological medicinal products obtained on the basis of medicinal plant raw materials.